Lipid extraction from thermal Fenton reaction in hybrid liquid biphasic system for biofuel and rubber bio-additive compounds - Yew, Guo Yong (2021)
This thesis is focusing on utilization of lipid compound and exploring the extraction method for producing lipid compound in which could be used in biofuel and synthetic rubber polymer. The existing extraction technology which is energy intensive, high investment cost on equipment and multistep procedure in which reduced the efficiency of the overall production process. Besides, the cultivation process incorporating artificial intelligent for rapid detection and used of sustainable medium from waste materials (waste molasses) and less depend on chemical based of salt. The chlorella sp. of microalgae has been selected with high lipid contain (Chlorella sorokiniana CY-1) and rough survivability strain (Chlorella vulgaris FSP-E). The objective of the study is to develop a sustainable system for large scale production of lipid compound from microalgae and exploring the application from the lipid derived of fatty acids compound. Hybrid liquid biphasic system (HLBS) has been developed from this study for suiting in large scale of lipid production in 83.5% of lipid recovery from microalgae biomass. The HLBS has included the disruptive and extractive properties in a single system, where it has been reduced the overall process duration more than 30%. Furthermore, the system has been exploring for biofuel production and combining with a non-catalytic transesterification method. The yield of F.A.M.E C4, C6, and C10 at 8.2 mg/g, 0.33 mg/g and 0.24 mg/g respectively, the duration of the transesterification for biofuel production at 4 min for a batch with lipid to methanol ratio 1:6 pulse at 0.8 in a single step process. The analysis of the cultivation medium for microalgae has been incorporated by artificial intelligent (K-NN algorithm) from photo-to-properties by using waste molasses as medium with 1206.43 mg/L of dry cell weight, protein content improved for 20.6%, while the Ai algorithm assisted to reduce the dependency of analysis from spectrophotometer. In conjunction, the lipid compound was found to be incorporated with metal ions as promising cross-linking compound for synthetic polymer - carboxylated nitrile butadiene rubber, (XNBR) improved stability of the sulphur-less linker compound L-MBL at 10.85% and raise the tensile strength 8.71% (27.55 MPa) higher than Sulphur based of linker. Last but not least, the content has been highlighted the research achievement and future opportunities from current techniques and technology that developed.